The Coefficient Parallelisator Matrix: A Diagonal Similarity Operator for Symmetry Preservation in Knot Semantic Logic - Ja'faruddin, Ja'faruddin; Ashari, Nur Wahidin; Baharuddin, Baharuddin; Asyari, Syahrullah; Fadiyah, Wulan Nur; Farhan, Muhammad (Jurusan Matematika FMIPA UNM, 2025)
This study introduces the Coefficient Parallelisator Matrix (CPM) as a novel diagonal similarity operator designed to preserve structural and semantic symmetry within the framework of Knot Semantic Logic (KSL). The CPM formalizes the process of parallelization in linguistic and conceptual structures by transforming semantic matrices through similarity operations that maintain eigenvalues, determinants, and symmetry invariants. Each element of the CPM acts as a scaling coefficient, re- balancing semantic weights while conserving the overall interpretive equilibrium of the text. Mathematically, the transformation A′ = MAM−1 establishes a spectral equivalence between the original and parallelized structures, ensuring that both share identical eigen-spectra, determinant, and Hermitian invariants. This invariance reflects a form of semantic gauge symmetry, wherein the un- derlying topology of meaning remains stable despite local transformations in semantic intensity. Conceptually, the operator bridges linguistic theory, topology, and algebraic representation, providing a formal mechanism for analyzing reflective relations such as parallelism, chiasmus, and concentric composition. The findings extend the mathematical foundation of KSL by establishing the Coefficient Parallelisator as an analytical framework for quantifying semantic symmetry—enabling deeper integration between mathematical logic, structural linguistics, and computational semantics.